Madhumeh w.s.r. to Type 2 Diabetes Mellitus-A Review. - Nagar, Vanita; Sahu, Ajay Kumar; Upadhyay, Abhishek; Patidar, Deepika (International Research Journal of Ayurveda & Yoga, 2023)
A chronic metabolic condition with numerous etiologies, diabetes mellitus affects people all over the world. However, the prevalence of diabetes has increased recently, which is particularly troubling in developed countries. An estimated 537 million adults (20–79 years) were living with diabetes worldwide in 2021, of which 14% (74.2 million) were from India, the country with the second largest number of people with diabetes in the world. This number is projected to increase by 68% (124.9 million) over the next 25 years. More worryingly, slightly more than half (53.1%) of people with diabetes in India are unaware of their condition. The main causes of diabetes mellitus in the present period include an entirely sedentary lifestyle, eating a lot of junk food, and weight increase. Based on the symptoms, this metabolic condition is classified as Madhumeha in Ayurveda. It is a Vataja Prameha that develops as a result of different nidanas. As an outcome, Ayurveda should be considered for the treatment of diabetes mellitus.